Cracks in the internet's foundation: The future of the internet's infrastructure and global internet governance - Daniel Voelsen (Stiftung Wissenschaft und Politik (SWP), 2019)
The foundation of the Internet is showing cracks. Central elements of the Internet's infrastructure are the result of decisions made decades ago. Since then, however, the technical context has changed dramatically, as has the political significance of the Internet. Three conflicts over the future development of the Internet infrastructure are particularly important for German policy-makers. The first is about security and privacy in the Internet's addressing system, the so-called Domain Name System (DNS). Second, a conflict is building up over the security of the Border Gateway Protocol (BGP) - the protocol used to coordinate data traffic on the Internet. Third, the security and availability of submarine cables, which form the physical backbone of the global Internet, are proving increasingly problematic. If these conflicts remain unresolved, while at the same time the demands on the Internet continue to rise worldwide, the consequences for security, privacy, and economic development will be increasingly negative. Moreover, the Internet is in danger of being split, all the way to the infrastructure level. This multifaceted field of conflict demands a clear strategic approach from German policy-makers. In accordance with their own digital policy demands, they should at the same time pursue the goal of worldwide interoperability and address the issues described within a European framework. The challenge here is to shape the further development of the Internet infrastructure in Europe in such a way that it complements - and does not further jeopardise - the shared global foundation of the Internet.
Keywords: 320